Batten disease through different in vivo and in vitro models: A review. Issue 3 (26th November 2022) - Nittari, Giulio; Tomassoni, Daniele; Roy, Proshanta; Martinelli, Ilenia; Tayebati, Seyed Khosrow; Amenta, Francesco
Abstract: Batten disease consists of a family of primarily autosomal recessive, progressive neuropediatric disorders, also known as neuronal ceroid lipofuscinoses (NCLs). These pathologies are characterized by seizures and visual, cognitive and motor decline, and premature death. The pathophysiology of this rare disease is still unclear despite the years of trials and financial aids. This paper has reviewed advantages and limits of in vivo and in vitro models of Batten disease from murine and larger animal models to primitive unicellular models, until the most recently developed patient‐derived induced pluripotent stem cells. For each model advantages, limits and applications were analyzed. The first prototypes investigated were murine models that due to their limits were replaced by larger animals. In vitro models gradually replaced animal models for practical, cost, and ethical reasons. Using induced pluripotent stem cells to study neurodegeneration is a new way of studying the disease, since they can be distinguished into differentiating elements like neurons, which are susceptible to neurodegeneration. In vivo and in vitro models have contributed to clarifying to some extent the pathophysiology of the disease. The collection and sharing of suitable human bio samples likely through biobanks can contribute to a better understanding, prevention, and to identify possible treatment strategies of Batten disease.